OPTIMIZATION OF TRAFFIC PUBLIC EDUCATION THROUGH POLICE GOES TO SCHOOL BY KAMSEL UNIT TO PREVENT TRAFFIC VIOLATIONS BY STUDENTS AT KARANGANYAR POLICE STATION - M. ALGHIFARI - (Police Studies Review, 2022)
ABSTRACT OPTIMIZATION OF TRAFFIC PUBLIC EDUCATION THROUGH POLICE GOES TO SCHOOL BY KAMSEL UNIT TO PREVENT TRAFFIC VIOLATIONS BY STUDENTS AT KARANGANYAR POLICE STATION M. Alghifari, 18.087, malghifari1999@gmail.com This research was motivated by increased traffic violations by students at Karanganyar Police Station. The National Police in accordance with its main duties and functions has a responsibility in reducing and preventing these problems. Kamsel unit as the task of providing information about traffic security, safety, and order to the community, especially students in police goes to school activities to prevent traffic violations by students. This research aims to describe the implementation of Police Goes to School activities in the legal area of Karanganyar Police and to describe the optimization of Police Goes to School activities to prevent traffic violations by students in the karanganyar police jurisdiction. This research is carried out with a qualitative approach, using field resarch research methods, data validation by data triangulation and data collection techniques with interviews and observations. The implementation of Police Goes to School is analyzed with management theory that can look at the stages of planning, organizing, implementation and control. While the influencing factors are analyzed using SWOT theory both factors that support and hinder the implementation of Police Goes to School. Then to optimize used knife analysis management theory such as POAC management function and management element 6 M. Based on the results of research on the implementation of Police Goes to School and optimization carried out by the kamsel unit has not been optimal. In the factual conditions of the implementation of Police Goes to School, it was found that there was a problem of the absence of standard operating procedures as implementation guidelines. Then the problem of the limitations of kamsel unit members, the limitations of facilities and infrastructure owned by the kamsel unit, and the non-achievement of the target where all students in the karanganyar police jurisdiction. Therefore, there needs to be a problem solving or solution in optimizing the activities of Police Goes to School in preventing traffic violations by students.